Differential Diagnosis of Intimal Flap in Type B Aortic Dissection. (August 2021) - Moral, Sergio; Cuéllar, Hug; Ballesteros, Esther; Burcet, Gemma; Evangelista, Arturo
Abstract : Supplemental Digital Content is available in the text.